Fundamental Movement Skills and Moods as Predictors of Games Performance in Primary School Students (Department of Physical Education, Sport, Health and Recreation, 2018)
The purpose of this study was to determine how far FMS and mood contribute toward games performance on elementray school student through invasion games activities (modified soccer and handball games). This research uses a correlational explanatory and regression . Third grade elementary school students (n=40) were enrolled in this study consisting of 21 male students and 19 female students. To determine the games perfromance using The Games Performance Assessment Instrument (GPAI) and Brief Mood Introspection Scale (BMIS) to measure the mood of the students. The result showed that FMS and positive moods contributed toward games performance on both games.